Salafi social and political movements: national and transnational contexts - Bano, Masooda (Edinburgh studies of the globalised muslim world, 2021)
Examines the impact of reforms within Saudi Arabia on Salafi intellectual thought, dawa movements and Jihadi groups Explores the factors shaping social liberalisation within Saudi ArabiaPresents examples of reforms within Salafi intellectual thoughtShows dynamism and adaptability within Salafi da‘wa movements in different country contextsAddresses the critical question of growing infighting within Salafi jihadi groupsThis book introduces the history of the rise and spread of Salafism during the 20th century as a global Islamic reform movement. It also explains Salafi tools of methodological reasoning: traditionally used to justify highly conservative positions, they now appear equally effective in defending more liberal life choices. The collection will help readers to appreciate the diversity of Salafi movements, as well as the significance of the ongoing socio-economic and political changes within Saudi Arabia and the wider Muslim world that are enabling shifts to this conservative Islamic scholarly tradition.Starting in late 2017, Saudi Arabia embarked on a series of reforms reversing many socially restrictive policies long associated with Salafism. These developments have triggered critical questions about the future of Salafism, crucially: is this the end for the most influential puritanical Islamic reform movement of the 20th century?